Study on the changes and influencing factors of depression in Chinese women with cancer: an analysis based on CHARLS panel data - Wang, Na; Chang, Mengran; Liu, Shidong; Chen, Bing (Frontiers in Public Health, 2025)
BackgroundThe social problems caused by depressive disorders and psychological behaviors in women are increasingly prominent, with extreme incidents occurring from time to time. Therefore, the issue concerning “how to prevent and resolve the risk of depression in women” is gaining significant attention across various sectors. However, previous studies have largely focused on teenage girls, perimenopausal women, or women during pregnancy and the postpartum period, neglecting the adverse effects of major diseases, which is detrimental to enhancing the psychological well-being of women with cancer.ObjectiveBased on cancer impacts, this study aims to clarify the depressive state, development trends, and influencing factors in Chinese women with cancer, a group particularly susceptible to depression, to provide decision-making references for improving their psychological well-being.MethodsUsing follow-up panel data from five waves of China Health and Retirement Longitudinal Study (CHARLS), Chinese women with cancer who had complete observed values were selected as research subjects. After data cleaning, a balanced short panel dataset containing 1,030 samples was obtained. The depression characteristics and development trends in women with cancer were analyzed using the panel statistical method, and the influence of socio-demographic factors was examined using a panel stochastic trend model.ResultsThe overall depression of Chinese women with cancer has deteriorated, putting them at risk of moderate depressive disorder. The development trend shows an inverted “U” curve, with significant differences observed among various groups based on urban and rural residency, educational levels, and regional locations. Specifically, urban women with cancer show milder depressive symptoms than those in rural areas, and women in the eastern region, those with higher educational levels, and those with non-reproductive system cancers show milder depressive symptoms than those in the central and western regions, those with lower educational levels, and those with reproductive system cancers. Regression analysis indicates that socio-demographic factors significantly influence depression in women with cancer. Among these influencing factors, age, having a spouse, high educational level, good performance in the activity of daily living (ADL), frequent visits to neighbors, and regular exercise are protective factors against depression, while diabetes, dyslipidemia, frequent outpatient visits, frequent hospitalizations, smoking, and low life satisfaction are risk factors for depression.ConclusionThe depressive state among Chinese women with cancer is alarming. In view of this, there is an urgent need for introducing more supportive policies aimed at improving psychological health, developing tailored measures to address the specific needs of different groups, intensifying efforts to standardize the diagnosis and treatment of depression, particularly for those in rural areas, central and western regions, and among individuals with lower educational levels. Additionally, the role of social participation activities, such as visiting neighbors and exercising, should be given full play to alleviate depressive symptoms.